Demographic and clinical characteristics of hospitalized children with suspected and laboratory-confirmed COVID-19 during the six waves of SARS-CoV-2 infection in northern Iran a retrospective cohort study - Mohammadi, Mohsen; Hashemi, Erfan; Shirafkan, Hoda; Sadeghi, Farzin; Yahyapour, Yousef (Frontiers in Pediatrics, 2024)
Introduction Northern Iran is one of the regions of the country most affected by COVID-19. The aim of the current study was to examine the demographics, clinical characteristics, and outcomes of suspected and laboratory-confirmed patients <18 years of age hospitalized over two years (during six waves of SARS-CoV-2). Methods This retrospective cohort study examined hospitalized patients with suspected SARS-CoV-2 infection in Babol, northern Iran. The study included patients <18 years of age admitted to a pediatric referral hospital from March 7, 2020 to March 20, 2022. Epidemiological and demographic characteristics, real-time PCR cycle threshold (Ct), clinical data and COVID-19 results were analyzed in the hospitalized patients. Results Totally, 2,731 patients with suspected COVID-19 were examined from March 2020 to 2022, with a mean age of 4.6 years, and were male (54.3%). Most suspected cases occurred during the fifth (Delta) and sixth (Omicron) relapse (30% and 20%, respectively). Among them, 461 patients had comorbidities, with brain and neurological diseases (BND), malignancies and hematopoietic and blood disorders (HBDs) being the most common (6.7%, 2.6% and 2.1%, respectively). Real-time RT- PCR showed that 391 patients were positive. The mean age of the positive patients was 5.2 years. Most positive cases were in the fifth wave (30.9%), male (53.7%) and 1–5 years old (49.1%). BND (9.5%) and cardiovascular diseases (CVD) (4.3%) were common underlying conditions. A higher viral load (Ct score = 9–20) was most common in the fifth wave. Moreover, 8.7% of ICU admissions and 2.4% of deaths were due to a Ct score of 9–20. Most deaths occurred in the 1–5 age group and were associated with BND. More deaths occurred in women (73.9% overall, 71.4% real-time RT- PCR -positive), and the highest mortality was in the fifth wave. The risk ratio of mortality was higher in children with kidney disease (KD) and BND. Conclusion There were 27 ICU admissions (6.9%) and seven deaths (1.8%). The current study also revealed that children of any age can be susceptible to SARS-CoV-2 infection, while children aged 1–5 years are more susceptible to COVID-19. The Delta variant is associated with higher rates of hospitalization and ICU admission, and the presence of BND is associated with higher mortality rates.